‘Amr Style in The Kitab al-Arba’in an-Nawawiyyah (Study of ‘Ilm Ma’ani): Gaya Bahasa Amr dalam Kitab Al-Arba’in An-Nawawiyyah - Afif Muttadin Munir; Yusroh; Thonthowi (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2022)
This paper aims to explain the form and meaning of the amr language style in the Kitāb Al-Arba’in An-Nawāwiyyah by Al-Hafizh Abu Zakariya Yahya bin Syaraf An-Nawawi from the perspective of Ma’ani science. The author uses a descriptive-qualitative method with the Ma’ani Science approach to analyze the form and meaning of the amr language style contained in the Kitāb Al-Arba’in An-Nawāwiyyah. The results of this study indicate that from the aspect of the tool shape and the meaning of the amr language style context, there are 27 data that use three forms of amr language style. The three styles of language are 1) فعل الأمر (command verb), 2) الفعل المضارع المقرون بلام الأمر (fi’il mudhari’which is preceded by lam command), 3) اسم فعل الأمر (isim  fi’il amr) two data. As for the meaning of the amr language style, the five meanings of the language style are 1) The meaning of إرشاد (irsyad / guidance), 2) The meaning of دعاء (du'a / request), 3) Meaning of التخيير (takhyir / choice), 4) Meaning of التهديد (tahdid / threat), and 5) The original meaning.